Factors Influencing Discharge Disposition After Ankle Arthrodesis. (June 2014) - Menendez, Mariano E.; Bot, Arjan G. J.; Neuhaus, Valentin; Ring, David; Johnson, A. Holly
Background: Although functional and morbidity outcomes following ankle arthrodesis have been widely studied, patterns of health care resource utilization remain unclear. The purpose of this study was to identify preoperative and postoperative risk factors for nonroutine discharge following ankle arthrodesis. A secondary study aim was to determine risk factors associated with prolonged hospital stay. Methods: Using the National Health Discharge Survey (NHDS) database for the years 2001 through 2007, an estimated 40 941 patients having undergone ankle arthrodesis were identified and separated into those who were discharged to home (routine discharge) and those who were discharged to rehabilitation facilities (nonroutine discharge). Factors influencing discharge disposition and hospital length of stay were determined using multivariable binary logistic regression analysis. Results: Risk factors for nonroutine discharge were increasing age, male sex, diabetes mellitus, atrial fibrillation, more than 1 general or surgery-related complication, additional days of care, and the 2005 to 2007 time period. Risk factors associated with prolonged hospital stay were advanced age, female sex, diabetes mellitus, more than 1 general or surgery-related complication, and the 2001 to 2004 time period. Conclusion: Early identification of these factors might prove useful for better allocation of resources and implementation of effective strategies aimed at preventing longer hospitalizations and nonroutine discharges in selected patients at risk. Level of Evidence: Level II, prognostic study.